TP53 Arg72Pro polymorphism (rs1042522) and risk of endometriosis among Asian and Caucasian populations. (June 2015) - Li, J.; Chen, Y.; Mo, Z.; Li, L.
Abstract: This study was conducted to investigate the association between TP53 Arg72Pro polymorphism (rs1042522) and risk of endometriosis. Studies were retrieved from Pubmed, Embase and HuGENet, and four models [dominant (AA + AG vs. GG), recessive (AA vs. AG + GG), co-dominant (AA vs. AG, AA vs. GG) and allele analysis (A vs. G), combined with odds ratios (OR) and 95% confidence intervals (CI)], were applied to evaluate this association. Fourteen eligible studies from eight countries were included. The pooled analysis identified a significant association between TP53 Arg72Pro polymorphism (rs1042522) and risk of endometriosis [dominant: OR 0.746, 95% CI 0.585–0.952, I 2  = 59%; recessive: OR 0.650, 95% CI 0.510–0.829, I 2  = 73%; co-dominant (GG vs. GC): OR 0.676, 95% CI 0.637–0.851, I 2  = 67%; co-dominant (GG vs. CC): OR 0.564, 95% CI 0.395–0.806, I 2  = 74%; allele analysis: OR 0.762, 95% CI 0.654–0.888, I 2  = 71%]. In the subgroup analysis, the same positive associations were found among Asians. After removing studies that did not satisfy Hardy–Weinberg equilibrium, significant correlations were confirmed in both the pooled analysis and the Asian subgroup. Three bioinformatic methods (TagSNP calculations, functional prediction and linkage disequilibrium analysis) were used to determine the importance of TP53 Arg72Pro polymorphism (rs1042522), and suggested that this locus may be equally important regardless of ethnicity. In conclusion, TP53 Arg72Pro polymorphism (rs1042522) was positively associated with risk of endometriosis, particularly among Asians. However, its potential role in Caucasians should not be ignored.